TOPIC: THE HAIRSTYLE IN ARTISTIC IMAGERY (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines the role of hairstyle in the creation of artistic imagery in literature. A hairstyle is not merely a physical detail of appearance; it serves as an aesthetic and symbolic element that reveals a character’s inner world, social status, cultural background, and psychological state. Using examples from Uzbek and world literature, the study analyzes how hairstyle functions as a meaningful artistic device in shaping literary characters.